1996
DOI: 10.1007/bf02630732
|View full text |Cite
|
Sign up to set email alerts
|

Urinary malondialdehyde and 8-hydroxydeoxyguanosine as potential markers of oxidative stress in industrial art glass workers

Abstract: Previous epidemiological studies have indicated that industrial art glass workers have increased mortality risks for certain types of cancer and for cardio- and cerebrovascular disease. To test the hypothesis that increased oxidative stress might contribute to these increased mortality risks, the urinary levels of the lipid peroxidation product, malondialdehyde (MDA), and the oxidative DNA adduct, 8-hydroxydeoxyguanosine (8OHdG) were determined in 343 workers (230 men and 113 women) from the art glass industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…It has also been widely used as a health effect marker for workers who have been exposed to chemicals [4][5][6][7][8][9] . Urinary 8-OHdG is stable when stored at 4°C for 19 days 10) , and also after 6 years of storage at Field Study -20°C 11) , but to our knowledge there is no report about its stability at room temperature, that is 25°C.…”
mentioning
confidence: 99%
“…It has also been widely used as a health effect marker for workers who have been exposed to chemicals [4][5][6][7][8][9] . Urinary 8-OHdG is stable when stored at 4°C for 19 days 10) , and also after 6 years of storage at Field Study -20°C 11) , but to our knowledge there is no report about its stability at room temperature, that is 25°C.…”
mentioning
confidence: 99%
“…As a result of exposure to ROS, 8-OHdG can be excised with hydroxylation by constitutive enzymatic repair systems and excreted in the urine (Shigenaga et al, 1989;Floyd et al, 1990;Fraga et al, 1990). Urban air pollution, tobacco smoke, environmental tobacco smoke (ETS), VOCs, and ionization radiation have been associated with the rise of urinary 8-OHdG levels (Samet et al, 1987;Anderson et al, 1991;Wilson et al, 1993;Tagesson et al, 1995Tagesson et al, , 1996Calderon-Garciduenas et al, 1999;Carstensen et al, 1999).…”
mentioning
confidence: 99%
“…Epidemiological studies have indicated that industrial art glass workers have increased mortality risks for certain types of cancer (stomach, colon, lung, skin, and brain) and for c ar di o va s c u l a r a n d c e r e b r o va s c u l a r disease. 11,12,13,14,15,16,17 The International Agency for Research on Cancer (IARC) has determined that the manufacture of art glass entails exposures that are probably carcinogenic to humans. 18 Glass blowing is one major occupation in the art glass industry which shows an increased cancer risk, possibly because the blow pipe introduces the potential for oral exposure.…”
Section: Chemical Agentsmentioning
confidence: 99%